The effects of contralateral limb cross-education training on post-surgical rehabilitation outcomes in patients with anterior cruciate ligament reconstruction: a randomized controlled trial - Chao Liu; ShiJia Li; JianPing Li; HongHao Zhang; GuQiang Li; XiangZhan Jiang (Journal of Orthopaedic Surgery and Research)
Abstract Objective This study examines whether cross-education training of the healthy limb promotes cross-transfer through central nervous system stimulation, enhancing the function, kinematic parameters, dynamic balance, and plantar pressure of the affected knee joint in patients recovering from postoperative anterior cruciate ligament reconstruction (ACLR). Methods Forty anterior cruciate ligament reconstruction (ACLR) patients, 5–6 weeks postoperatively, were included and randomly assigned to either an experimental group (n = 20) or a control group (n = 20). The experimental group participated in six weeks of cross-education (CE) training in addition to conventional rehabilitation, while the control group received only conventional rehabilitation. Assessment outcomes included knee function (Lysholm score, joint mobility, and surface electromyographic characteristics of the rectus femoris muscle), kinematic parameters (stride length, stride speed, and stride width), dynamic balance (gait line length, single-support line length, and medial-lateral displacements), and plantar pressure (forefoot, midfoot, and hindfoot pressures). The effect of CE training on postoperative ACLR rehabilitation was comprehensively assessed by comparing the pre- and post-intervention changes within each group and the differences between the groups. Results Before the intervention, no statistically significant differences were observed between the two groups across all measured parameters (P > 0.05). Following the intervention, significant improvements in knee function, kinematic parameters, balance function, and plantar pressure were observed in both groups, with the experimental group showing significantly more significant improvements (P < 0.05). The Lysholm score, range of motion (ROM), and surface electromyographic activity of the rectus femoris muscle were significantly higher in the experimental group compared to the control group (P < 0.01). Among kinematic parameters, the experimental group demonstrated a significant increase in stride length and reduced stride width, whereas differences in stride speed were not statistically significant (P > 0.05). Regarding balance function, the experimental group exhibited significantly longer gait and single-support line lengths, significantly reducing medial-lateral displacement (P < 0.05). Analysis of plantar pressure revealed significant improvements in forefoot and hindfoot pressures in the experimental group, with a particularly notable increase in hindfoot pressure (P < 0.05). However, changes in midfoot pressure were not statistically significant (P > 0.05). Conclusion CE training markedly enhanced knee function, kinematic metrics, dynamic stability, and plantar pressure in postoperative ACLR patients providing initial evidence for the prospective utilization of CE theory in rehabilitation. Nonetheless, the fundamental mechanics of its effects remain ambiguous, and variables such as individual differences and neuromuscular adaptation processes may affect training results. Future studies should examine its long-term impacts and uncover potential neuromuscular pathways to establish a solid scientific basis for improving postoperative rehabilitation procedures.